Real-world survival of model-3501 subcutaneous implantable defibrillator lead. (19th May 2022) - Viani, S; Segreti, L; Ottaviano, L; Biffi, M; Nigro, G; Ricciardi, G; Francia, P; D'onofrio, A; Bisignani, G; Dello Russo, A; De Filippo, P; Solimene, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In December 2020, the subcutaneous implantable cardioverter-defibrillator (S-ICD) lead model-3501 was subject to a safety notification because of increased risk of fracture at a location just distal to the proximal sense ring. The manufacturer's product performance report currently reports a lead survival probability of 98.8% at 45 months. However, no multicenter long-term performance information exists for this lead. Purpose: Our aim was to assess the longevity of model-3501 leads and to compare it with that of the previous model-3401. Methods: This analysis included consecutive patients who received an S-ICD with a model-3501 or a model-3401 lead at 66 Italian participating centers of the Rhythm Detect registry. A lead failed if it required extraction/replacement because of abnormalities suggestive of a structural defect, e.g. out-of-range impedance, nonphysiological electrical noise or ineffective therapy. Results: From January 2013 to July 2021, 2403 patients were implanted and followed up (78% male, age 49±15years, ejection fraction 45±16%, body mass index 26±4Kg/m2). A 3501-model lead was used in 1697 patients and a 3401-model in 706 patients. During a median follow-up of 38 months [25th–75th percentile: 24-55], we detected 4 malfunctioning model-3501 leads and 2 model-3401 leads. After analysis of the returned leads by the manufacturer's technical services, a single model-3501 lead failure was a fracture distal to the proximal ring electrode, as described in the manufacturer's advisory letter. No deaths or permanent injuries occurred as a result of lead failures. The survival of 3501-model leads at 4 years was 99.5% (95% confidence interval, 99.0 to 99.9) compared with 99.9% (95% confidence interval, 99.6 to 100.0) of 3401-model leads (p=0.110). The cumulative occurrence rate of the 3501-model safety notification fracture was 0.1% (95% confidence interval, 0.0 to 0.3). Conclusions: In this large multicenter analysis, the survival probability of model-3501 S-ICD leads was in line with that reported by the manufacturer, was not significantly lower than that of 3401-model leads (not affected by a safety notification), and still higher than that reported with transvenous leads. Although an enhanced electrode is now available, which addresses the potential for electrode body fracture, the present findings are reassuring and may have significant implications for the management of patients who have affected leads.